CLINICAL, HEMATOLOGICAL AND RISK FACTORS ASSOCIATED WITH BORRELIOSIS IN HORSES FROM SAO PAULO, BRAZIL - BASILE, R. C.; VIEIRA, M. R.; DEL RIO, L. A.; DE BONIS, T. C.; AMARAL, G. P. D.; JANINI, A. P. R.; GUERESCHI, l. F.; MANTOVANI, E.; BONOLDI, V. N.; YOSHINARI, N. H.; SOARES, V.; MACORIS, D. G.; et al. (Ars Veterinaria, 2021)
Lyme borreliosis is caused by Borrelia burgdorferi sensu lato and affects humans and many other mammals, including horses. This disease is poorly studied and reported in horses, and epidemiological surveys are required to provide more precise information about the course of the disease. The aims of the present study were to determine the prevalence of seropositive horses for Borrelia burgdorferi sensu lato in São Paulo State, Brazil and to collect data on possible risk factors associated with the disease along with clinical and hematological changes in seropositive horses. There was verified that there was a high correlation between the occurrence of seropositive horses infested with Amblyomma sculptum ticks and the presence of capybaras on the property as well as the occurrence of abortion and retained placenta in mares. In terms of hematological alterations, the occurrence of lymphopenia was observed in seropositive animals. Borreliosis in horses from São Paulo, Brazil can be associated with presence of Amblyomma scupltum ticks, proximity with capybaras and can be manifested as alterations in reproduction of mares and lymphopenia.